STRATEGI DAKWAH USTADZ DATUAK MONGGUANG DALAM KAJIAN SUBUH DI SURAU MUDIAK JORONG MAUR KECAMATAN MUNGKA - Rahma Hasanah; Tomi Hendra (Universitas Pahlawan Tuanku Tambusai, 2022)
The current development of Islam is inseparable from da'wah activities as supporting activities for the spread of Islamic teachings, in addition to inviting and calling people to the way of God, da'wah also plays an important role in increasing faith and religious-based understanding of the goals of da'wah. Subuh study activities are one of the means for conveying Islamic values, Ustadz Datuak Mongguang broadcasts da'wah in the midst of people who need solutions to every problem in their lives, by inviting people to first strengthen the foundations of faith and draw closer to Allah to make the congregation interested in participating in Subuh studies. Of course, to invite and convey da'wah messages to mad'u, the right strategy is needed so that the da'wah targets are interested in being involved in da'wah activities. This study aims to reveal in-depth social phenomena about Ustadz Datuak Mongguang's Da'wah Strategy in the Fajr Study at Surau Mudiak Jorong Maur Subdistrict, Mungka District by using Abu Al-Fath Al-Bayanuni's theory of da'wah strategies carried out using a descriptive qualitative approach. The results of this study indicate that the da'wah strategy used by the Ustadz in his Subuh Study includes Sentimental, Rational and Sensory strategies which are implemented in the form of discussion and question and answer lecture activities Keywords: Da'wah Strategy, Dawn Studies